Effects of dietary L-leucine supplementation on testicular development and semen quality in boars - Lin, Yan; Li, Jiayi; Wang, Ke; Fang, Zhengfeng; Che, Lianqiang; Xu, Shengyu; Feng, Bin; Zhuo, Yong; Li, Jian; Wu, De (Frontiers in Veterinary Science, 2022)
Sperm and seminal plasma are rich in leucine, and leucine can promote the protein synthesis. This property makes it an interesting amino acid to increase sperm quality of human and livestock spermatogenesis. The goal of this study was to explore the effects of dietary leucine supplementation on testicular development and semen quality in boars from weaning to 10 months of age. 30 pure-bred, weaned Duroc boars (8.0 ± 1.0 kg) were randomly divided into two groups: control group (CON; fed the basal diet) and leucine group (LEU; fed the basal diet supplemented with 1.2% leucine); then, their body weight and testicular volume were recorded every 4 weeks. Testes were collected for histological and genes expression analysis from 150-day-old boars. Semen was collected and analyzed. Amino acids contents of blood plasma, seminal plasma, sperm, and testes were determined. Dietary supplementation with leucine increased the testicular volume and weight of boars, compared with CON. Sperm viability, sperm count per ejaculation, and average curve speed of sperm in leucine-supplemented boars were increased. Furthermore, leucine supplementation increased the blood plasma and seminal plasma leucine concentrations, and enhanced the gene expressions of branch chain amino acid transaminase, protein kinase B, mammalian target of rapamycin (mTOR), and cyclinb1 in the testes. Interestingly, the expressions of the p-mTOR and mTOR proteins in the testes were also upregulated. Thus, dietary leucine supplementation increased leucine absorption and utilization in the testes, promoted testicular development, and improved semen quality of boars, partly through the mTOR signaling pathway.